Preispolitik für ökologische Lebensmittel: Eine neo-institutionalistische Analyse; Price Policy for Organic Food: a Neo-institutional Approach - Achim Spiller (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2001)
– Price premiums are recognized as a central barrier for the diffusion of organic food. On average, the consumer has to pay about 50 % more for organic food than for comparable products. This is also true for large retailers although considerable economies of scale could be expected. Against this background the following article analyzes pricing strategies of supermarkets. It appears evident that higher prices of organic food reflect higher costs of production and lower output, but primarily this is due to inefficient structures in processing and marketing. Furthermore, the pressures of competition in the market are low; price reductions and bargain sales are avoided by competitors. If the premium prices are compared with the results of market research, a large discrepancy between the willingness to pay for organic food and actual prices will be found. By means of a conjoint analysis the managerial inefficiencies of this pricing policy can be proven. Finally, the paper gives theoretical justification for the current pricing policy of large retailers. We present a neo-institutional organizational approach to identify reasons for imitative behaviour. Similar pricing strategies of all retailers can be considered as a process of mimetic isomorphism. Particular emphasis is placed on high managerial uncertainty and pressure of stakeholders.
Keywords: 330